The Influence of Job Satisfaction and Organizational Commitment on Employee Loyalty at Capella Ubud Bali - Widyaningsih, Ni Luh Nyoman; Diwyarthi , Ni Desak Made Santi; Sulistyawati, Ni Luh Ketut Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Decreasing employee loyalty can be a problem for the company, this is related to the increase in turnover rates where companies must re-recruit to ensure the sustainability of the company's operations. The purpose of this study was to test partially and simultaneously the effect of job satisfaction and organizational commitment on employee loyalty at Capella Ubud Bali. To collect data, questionnaires were distributed to 59 respondents. The t-test, coefficient of determination test, classical assumption test and F-test were used to analyze the data. Based on the data analysis, the results of Job Satisfaction and organizational commitment with partial have a good and significant impact on Employee Loyalty. In addition, with the simultaneous job satisfaction and organizational commitment also have a significant impact on employee loyalty. Together they contribute to influencing Employee Loyalty by 66.4% which is included in the category of strong influence.